2018
DOI: 10.3233/ais-180504
|View full text |Cite
|
Sign up to set email alerts
|

Designing interactive public displays in caring environments: A case study of OutLook

Abstract: In the past decades, we have witnessed a proliferation of interactive public displays for advertisement, entertainment and exhibition. We believe they also have great potential in the public spaces of caring environments if supported by related knowledge of design and research. This study explores how to design and evaluate interactive public displays in caring environments with a case study. In this paper, we describe the design process of OutLook, which is part of an initial participatory system specially de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…At the home level, our findings point to potential strategies related to the built environment, care philosophy, human resources (e.g., training, hiring, and retention), communication and staff roles and responsibilities within the home. Other innovations, such as incorporating creative art 72 and technology installations, 73 although not included in our review, may also present promising approaches. While our review was initiated before the COVID‐19 pandemic and the included studies did not occur or discuss their findings in the context of pandemics or infectious disease outbreaks, COVID‐19 highlighted social connection as an important public health issue for nursing homes.…”
Section: Discussionmentioning
confidence: 99%
“…At the home level, our findings point to potential strategies related to the built environment, care philosophy, human resources (e.g., training, hiring, and retention), communication and staff roles and responsibilities within the home. Other innovations, such as incorporating creative art 72 and technology installations, 73 although not included in our review, may also present promising approaches. While our review was initiated before the COVID‐19 pandemic and the included studies did not occur or discuss their findings in the context of pandemics or infectious disease outbreaks, COVID‐19 highlighted social connection as an important public health issue for nursing homes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, smart environments provide additional visualization capabilities that could be used to provide feedback to the human, e.g. visual displays integrated into the environment [6,20].…”
Section: Interaction In Smart Environmentsmentioning
confidence: 99%
“…Our research mainly followed another direction where the explorations aimed to influence residents' social behavior or feelings by designing shared displays [14]. [13]. Both of the case studies conducted field trials and found a similar problem that many residents tended to passively watch instead of actively interacting with the displays.…”
Section: Motivation From Previous Workmentioning
confidence: 99%